English as a Second Language (ESL) Learning: Setting the Right Environment for Second Language Acquisition - Hashim, Haida Umiera; Yunus, Melor Md (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
Early exposure to English is very important as it is crucial for learners to acquire English language at early age as English is a global language that is used not only in the level of primary and secondary school but also in tertiary level of education. Schools can be one of the important roles in influencing second language acquisition, particularly English language. However, most schools did not consider acquiring English from the perspective of learners’ fluency and rarely consider movements or approaches that they can take to improve ESL learning among students. This study intended to investigate the influence of school settings and routines on ESL learning among secondary students. A qualitative method is used in this study as data were collected through the method of observation and interview. The observation period throughout the process of collecting data has been conducted based on a field note specifically prepared for this study. The participants involved in this study were all-girl school students located in Selangor. The gathered data were then interpreted in the findings analysis. Based on this study, it was proven that there are co-relations between the school settings and routines on ESL learning among secondary students. It was found that school settings and routines do influence ESL learning among secondary students. Discussion and recommendations are further explained in this study. Thus, it is hoped for future researchers to conduct further research on related factors that might help to contribute in ESL learning among ESL learners.